INTEGRATIVE BIOMEDICAL EDUCATION: DEVELOPING SPIRITUAL AND PROFESSIONAL MATURITY THROUGH BIOLOGICAL KNOWLEDGE - Xudoykulova Nasiba Ismailovna (Bright Mind Publishing, 2025)
The article examines the concept of integrative biomedical education as a modern pedagogical model that connects biological sciences with the moral and professional development of future medical specialists. It argues that biological knowledge serves not only as the foundation of medical competence but also as a means of shaping ethical responsibility, empathy, and spiritual maturity. The study proposes an interdisciplinary framework where biomedical understanding is harmonized with humanistic pedagogy to form a holistic, value-oriented professional identity. Through this integration, medical education becomes a platform for cultivating both intellectual excellence and moral consciousness in students.
Keywords: integrative biomedical education, biological knowledge, moral development, professional maturity, humanistic pedagogy, medical ethics, interdisciplinary learning, value-based education.